“You see how good-looking Lee Ann is!” Establishing field relations through gendered and racialised bodily practices - Spanger, Marlene (Qualitative Studies, 2012)
By investigating the case of female Thai migrants selling sexual services in Denmark, I argue that ‘the victim’ versus ‘the empowered subject’ is an undesirable binary for analysing how female migrants perform gendered subject positions in their everyday life. The article suggests a poststructuralist feminist perspective, arguing that looks and bodily practices, based on different constellations of gender and sexuality and race and nationality, are important for the research situation. Bringing in two different examples, the article analyses the field relations, and the implied power relations, - between the researcher(s) and the studied subjects that are constituted through gender, sexuality, race and nationality. These relations form the premises for producing material.